The poetry of language. Regarding the creativity of words (ALPHA. Journal of Arts, Literature and Philosophy, 2020)
In this essay we explain and discuss the idea that language, beyond its quality of being a means of communication, manifests itself as poetry; in the sense that it is in language (and thanks to it) where the daily configuration of a world with human meaning takes place. The poetry of language appears as an expression that thrives to explain the creative energy of language, as it institutes reality in its linguistic dimension. The discussion take shape in the form of comments on, and dialogue with, thinkers such as Heidegger, Saussure, Benjamin, Maturana, and with poets such as Novalis, Neruda, Huidobro, with the purpose of elucidating the poetic dimension of language and its practical and moral effects on social life.
Keywords: Poetry of language; creativity; linguistic poiesis; being and poetry